Representations of the foreign and self-representations in language classes: theoretical and methodological approaches - López Bermúdez, Daniel Hernán (Rastros Rostros, 2024)
This article proposes some theoretical references and methodological suggestions on the subject of images of the foreign in language classrooms, or more precisely, on the representations of foreign cultures and about one’s own culture. In order to do this, a brief examination of the concept of social representations is taken as a starting point, and then it is regarded the applicability of this concept in the field of language didactics using an approach that advocates a reflexive look at one’s own culture and, at the same time, at foreign cultures: the diversified de- scription. This methodological approach aims to warn of the risks of a univocal and reductive vision on this subject, and to give an active and critical role to both the student and the teacher in the construction of self-images and images of the foreign. However, it is not a question of offering pre-established formulas but of presenting a range of conceptual and practical tools, which can be permanently expanded and adapted, in order to undertake a reflexive process that allows the (self-) representations to emerge, identify their sources and examine them with a relativizing view